EFEKTIVITAS TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION DAN MUSCLE ENERGY TECHNIQUE TERHADAP PERUBAHAN NYERI MYOFASCIAL TRIGGER POINTS MUSCULUS UPPER TRAPEZIUS: Efficacy of Transcutaneous Electrical Nerve Stimulation and Muscle Energy Technique on Myofascial Trigger Point Pain in the Upper Trapezius - Hasnia Ahmad; Abdullah Tamir; Siti Nurul Fajriah; Fahrul Islam; Hasbiah (Jurusan Fisioterapi Poltekkes Kemenkes Makassar, 2026)
Myofascial Trigger Point in the Upper Trapezius muscle is a musculoskeletal disorder characterized by a hyperirritable spot within a skeletal muscle, presenting as a hypersensitive nodule located in a taut band. This nodule is painful upon compression and can cause referred pain.This study aimed to determine the pain intensity of myofascial trigger points in the upper trapezius muscle before and after the application of Transcutaneous Electrical Nerve Stimulation (TENS) and Muscle Energy Technique (MET), as well as to ascertain the magnitude of the effect of TENS and MET on changes in myofascial trigger point pain in the upper trapezius.The research employed a Pre-Experimental design with a